Why Users Comply with Wearables: The Role of Contextual Self-Efficacy in Behavioral Change - Rieder, Annamina; Eseryel, U. Yeliz; Lehrer, Christiane; Jung, Reinhard (International journal of human-computer interaction, 2021)
Wearables provide great opportunities for improving personal health, but research challenges their capacity to evoke behavioral change effectively. Realizing the full potential of wearables requires a better understanding of users' behavior change processes. Based on self-efficacy theory, we investigate how wearables influence users' perceptions of their self-efficacy and subsequent health behavior. Using narrative interviews with twenty-five long-term wearable users, we show that wearables can have both positive and negative effects on users' perceptions of their self-efficacy and that these perceptions are subject to internal and external contexts, which can positively or negatively affect users' compliance. We also find that the internal context may have a compounding or neutralizing effect on self-efficacy, despite an adverse external context. Our study shows the contextual and transient nature of self-efficacy, thus contributing to self-efficacy theory and research on wearables and offering practical design implications.